Interdisciplinary Look at Lifestyles in School Population. Pereira - Enith, Velásquez-Restrepo Luz; Márquez-Galvis, Mónica M.; Arboleda-Amórtegui, Gleydis; Rodríguez-Amador, Tatiana; César, Zapata-Giraldo, Paulo (Journal of Ecohumanism, 2024)
This document presents the lifestyles of the student population enrolled in the Official Educational Institution. Pereira. Objective: To recognize lifestyles in the student population of the Educational Center 30 de Agosto, during the year 2018. Type of descriptive cross-sectional study, 49 boys and girls participated. Interdisciplinary research in Optometry, Respiratory Therapy, Radiology, and Diagnostic Imaging and Nursing, an instrument developed by the authors, validated by experts, allowed observing practices on Care and self-care. Results: Their families in 37% are extensive; Diet shows a high preference for foods rich in flour and sugar, they carry out physical activity. 47% of boys and girls have nighttime awakenings. 57% are taken to growth and development control. The use of insufficient protection elements; 99% do not report alcohol or tobacco consumption. Boys and girls collect and separate waste. Discussion: Vulnerable population, female population predominates in all age groups, there is a high preference for foods rich in flour and sugar, in tune with the diet of the region, the lack of restful sleep has consequences in the performance and development of activities daily as school activities, one of the important aspects in the studied population is the care habits they have and their permanence in them, in general, the evaluated aspects show difficulties in the self-care processes, the use of free time is compared with the unrelated physical activity as wellness in context. Conclusions: Diet suffers from deficiencies, consumption of sugary drinks, fats, flours, low intake of fruits and vegetables predominates, the sleep period is affected.